Testimony of memebr of Lithuanian Helsinky group dr. A. Stakevičius on the 15th of September in 1988 to USA Congress Commission on Security and Cooperation in Europe - Zizas, Rimantas (Genocidas ir rezistencija, 2003)
On 1 August 1975 the Soviet Union, together with other European countries, the US and Canada, signed the Final Act of the Conference on Security and Cooperation in Europe (CSCE) in Helsinki. This document set out the principles of European security and international cooperation in the fields of economy, science, technology, and environmental protection. The third part of the resolutions deals with humanitarian issues and human rights. The protection of human rights has come to be seen as a key element of European security and cooperation. In 1975, following the Helsinki Conference, the US Congress established the Commission on Security and Cooperation in Europe to collect testimonies and to verify the implementation of the resolutions of the Final Act of the Helsinki Conference. One of these testimonies was submitted to the Commission by a member of the Lithuanian Helsinki Group, Dr Algirdas Statkevičius, on 15 September 1988.